쥐에서 허혈 재관류 신장손상에 대한 반대편 신장의 허혈 선조정의 신장 보호효과 - 김대우; 최진우; 박연진; 주진덕; 강유진; 김용신; 전연수; 인장혁 (Korean journal of anesthesiology, 2007)
Background: Acute renal failure (ARF) results from renal ischemic reperfusion (IR) injury and is a major contributor to the morbidity and mortality encountered during the perioperative period. It was previously demonstrated that ischemic preconditioning (IPC) of the heart, brain, and kidney offered protection against IR injury. Therefore, this study examined whether or not distant IPC can also be effective against IR injury in other organs. Methods: C57BL6 mice were classified into three groups, Sham group (n = 7), IR group (n = 7) and Cross IPC IR group (n = 7). The sham group was subjected only to a right renal nephrectomy (ligation of renal pedicle with silk). The IR group was subjected to 30 min of left renal ischemia after a right nephrectomy. The cross IPC IR group was subjected to right renal IPC (two cycles of 5 min of ischemia and reperfusion) followed 15 min later by a right nephrectomy and 30 min left renal ischemia. The left kidney was harvested 24 h after surgery and the histology and blood creatinine level was analyzed. The left kidneys were isolated 15 min after right nephrectomy (sham, n = 7) and right renal IPC (cross IPC, n = 7), respectively, and analyzed by western blotting. Results: The level of the intra-cellular signaling proteins, iNOS, Akt and ERK increased significantly as a result of the right renal IPC, and the renal functions were well preserved in the cross IPC IR group compared with the IR group. Conclusions: Cross renal IPC offers protection by elevating the iNOS, Akt and ERK levels due to the distant oxygen free radicals stream against the opposite renal IR injury in mice. KCI Citation Count: 2